Boosting productivity and wellbeing through time management: evidence-based strategies for higher education and workforce development - Patzak, Alexandra; Zhang, Xiaorong; Vytasek, Jovita (Frontiers in Education, 2025)
IntroductionAmid increasing academic and professional pressures, time management is widely acknowledged as essential for supporting students' and professionals' well-being, motivation, and performance. However, despite general agreement on its benefits, there remains limited clarity about which specific time management strategies are most effective, particularly in the context of higher education and workforce development. Compounding this issue are inconsistencies in how time management is defined and measured across the literature.MethodThis systematic review synthesizes findings from 107 empirical studies—spanning higher education and workplace settings and including peer-reviewed journal articles and dissertations—to clarify the conceptual landscape of time management, identify high-impact strategies, and assess their influence on key outcomes. Following PRISMA guidelines, we conducted a comprehensive search across PsycINFO, ERIC, ProQuest Dissertations & Theses, and Google Scholar, including studies that employed quantitative, qualitative, and mixed-methods designs to ensure a broad and nuanced understanding of the topic.ResultsPlanning, goal-setting, prioritization, and task organization emerged as particularly beneficial strategies for enhancing productivity, well-being, and overall performance.DiscussionBy addressing definitional inconsistencies and identifying the most effective strategies, this review offers evidence-based guidance for educators, instructional designers, and career development professionals seeking to better equip students and workers for success in an increasingly demanding and competitive environment.